Factors Associated With Tolerance for In‐Office Laryngeal Laser Procedures. (6th January 2021) - Zheng, Melissa; Arora, Nikhil; Bhatt, Neel; O'Dell, Karla; Johns, Michael
Abstract : Objectives/Hypothesis: A variety of laryngeal pathologies are increasingly being managed with in‐office KTP laser (IOKTP) endoscopic procedures. The primary goal of this study was to identify patient characteristics and disease‐related features that correlated with tolerance for IOKTP. Study Design: Retrospective chart review. Methods: The study was a retrospective review of adult patients undergoing office‐based laryngeal laser procedures between November 2016 and December 2019 at a tertiary care center. Two blinded otolaryngologist reviewers scored videotaped recordings of IOKTP procedures and assessed severity and distribution of disease using a modified Derkay score, and evaluated procedure tolerance using a visual analog scale. Results: A total of 56 patients who received IOKTP procedures for laryngeal pathology were reviewed, 42 male and 14 female, with a mean age of 61 years. Gender, age, and BMI were not correlated with tolerance. There was a moderate, negative correlation between tolerance and total number of pathological anatomic laryngeal subsites (rs(56) = −0.35, P  = .01). There was a weak, negative correlation between tolerance and total modified Derkay score (rs(56) = −0.29, P  = .03). The median tolerance score was lower for patients with posterior lesions (Mdn = 6.4) compared with patients with non‐posterior lesions (Mdn = 7.4), P  = .04, and lower for current or former smokers (Mdn = 6.5) compared with never smokers (Mdn = 7.3), P  = .04. Conclusion: Patients with large disease burden or posterior lesions and patients with smoking history may exhibit poorer tolerance of IOKTP procedures, factors which can help guide pre‐procedural counseling and management decisions. Level of Evidence: IV Laryngoscope, 131:E2292–E2297, 2021